High strength and thermal stability of bulk Cu/Ta nanolamellar multilayers fabricated by cross accumulative roll bonding. (15th May 2016) - Zeng, L.F.; Gao, R.; Fang, Q.F.; Wang, X.P.; Xie, Z.M.; Miao, S.; Hao, T.; Zhang, T.
Abstract: Bulk Cu/Ta nanolamellar multilayers with an individual layer thickness from several micrometers down to 50 nm were successfully fabricated via a combination of cross accumulative roll bonding (CARB) and an intermediate annealing step. This fabrication technique allowed to effectively suppress the formation of plastic instabilities and edge cracks during the repeated rolling process. A transition of the layered morphology from non-planar interfaces at the submicron level to nearly planar interfaces at the nano-scale was observed with decreasing layer thickness. High resolution transmission electron microscopy, selected area electron diffraction and X-ray diffraction were performed, and the results indicate that the Cu/Ta nanolamellar multilayers with a layer thickness of 50 nm show a 100Ta [110]∥110Cu [111] rolling texture relationship. Tensile tests revealed that the ultimate tensile strength of the composite was up to 950 MPa, which is approximately 5 times higher than that of the initial pure Cu and Ta. The hardness of the prepared multilayer maintained unchanged even after an annealing at 500 °C for 1 h. These unique properties are attributed to an atomically flat bimetal interface and the low amount of homophase grain boundaries resulted from the CARB process. Graphical abstract: